Relationship Between Coexistence Styles and Social and Personal Indicators - Ascorra, Paula; Cárdenas Mancilla, Karen; Gálvez, Paula; Ávila, Alejandra; González, Carolina; López, Verónica (Revista de Psicología, 2021)
During the last 20 years, Chile has enacted a series of policies aimed at the development of school coexistence and participation. These policies have exhibited a hybrid character, with a preeminence of an order and security ap-proach to address conflicts, and few processes of participation and deliberation within schools. In this context, this study aimed to identify the approaches to school coexistence promoted by Chilean schools and determine the incidence of these approaches on national measurement indicators (school coexistence climate, and participation and citizenship training). A secondary analysis of two databases was carried out, considering descriptive, correlational, and multiple regression analysis. A total of 125 representative schools from three regions of the country participated. The results show a prevalence of school coexistence oriented to the reduction of violence or maintenance of peace, with a predictive value on the school coexistence climate indicator. Inclusive coexistence showed a predictive value on the indicator of participation and citizenship training. It is concluded that school coexistence in Chile is approached from a narrow perspective, focused on the maintenance of peace and not on the construction of a democratic coexistence that promotes lasting peace.